Enhancing Spiritual Literacy and Writing Creativity through Novel Review Learning Based on Carl Rogers’ Theory - Iwan Kuswandi; Sulistiyono; Nurulshahidah binti Hamdan; Amir Heidi bin Askomi (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2026)
This study aims to investigate strategies for addressing low student literacy and writing skills through a holistic approach that integrates literary text comprehension with the internalization of spiritual values, positioning novel review activities as an effective pedagogical intervention to enhance both spiritual literacy and creative writing competencies. This study employed a quantitative quasi-experimental design involving 30 students from TMI Al-Amien Prenduan, using literacy and spiritual literacy questionnaires administered before and after the intervention, and analyzed with a paired sample t-test to assess the effectiveness of novel discussion activities in enhancing spiritual literacy, moral reflection, and writing creativity. This study concludes that the novel discussion of Perempuan Sejuta Kepahitan significantly enhanced students’ Spiritual Literacy and Writing Creativity at TMI Al-Amien Prenduan, increasing mean scores by 14.33 points. Through interactive, learner-centered, and reflective experiences, aligned with Carl Rogers’ humanistic theory, students developed authentic self-expression, critical thinking, internalization of spiritual values, character formation, and holistic growth, with statistically significant differences between pre-test and post-test scores (Paired Sample t-Test, Sig. = 0.000), demonstrating the activity’s effectiveness as a pedagogical strategy.